Health risk assessment of drinking water in correlation with water-related diseasess - Kochubovski, Mihail; Stambolieva, Aleksandra; Kostova, Aneta; Chibisheva, Elena; Karadzovski, Zarko (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2020)
Healthy and safe drinking water in sufficient quantities provided to consumers improves living conditions, raises health culture at a higher level and promotes the environment as a whole. The aim is to see if there is a correlation between irregular water samples with intestinal infectious diseases related to drinking water. Materials and method. The preparation of the Republic Computer Program (1996) for issuing laboratory findings (RCP) from the analyses of samples of drinking water (physico-chemical and bacteriological), in accordance with the methodology for application of ID numbers in the computer system in the Public Health Centers has created the possibility of complete health records of drinking water supply facilities under health surveillance for the territory of the entire Republic. Evaluation has been made of the results of basic physicо-chemical and bacteriological analyses of drinking water in the settlements of the Republic of North Macedonia and the water-related diseases – waterborne intestinal infectious diseases in the period 2014-2018. Results. Drinking water from city water supply in the examined period in terms of physico-chemical analysis ranged 2.9-4.3%, while in relation to bacteriological analysis 0.9-2.6%.. Waterborne intestinal infectious diseases show a decline in their incidence in 2018. Conclusion. The registered data from the physicо-chemical and bacteriological analysis showed that the drinking water from the city water supply systems in the period 2014-2018 was safe. According to the processed data, access to safe drinking water for the population was 97% by 2018, which ranks the country in the group of countries in the world with the highest access to safe drinking water, and there is no significant connection with drinking water related diseases.
ПРОЦЕНКА НА ЗДРАВСТВЕНИОТ РИЗИК ОД ВОДАТА ЗА ПИЕЊЕ ВО РЕЛАЦИЈА СО БОЛЕСТИ ПОВРЗАНИ СО ВОДАТА